Pengaruh Penambahan Crude Fish Oil (CFO) pada Pakan Udang Vaname (Litopenaeus vannamei) Terhadap Kandungan Kolesterol dan Retensi Lemak Daging [ Influence of Addition Crude Fish Oil (CFO) in White Shrimp (Litopenaeus vannamei) Feed to Cholesterol Content and Fat Retention In Meat ] - Agustono Agustono; Widya Paramitha Lokapirnasari; Azharur Riyadh (Faculty of Fisheries and Marine Universitas Airlangga, 2015)
Abstract White shrimp are aquatic organisms consumed by many people and a source of animal protein and fat needed by humans. Shrimp also require fat as a source of energy and metabolic processes to maximize growth. White shrimp meat contains high cholesterol so that it becomes an obstacle to consume white shrimp and high cholesterol in feed can affect the growth of shrimp. This problem can be solved by adding Crude Fish Oil (CFO) which contain high omega-3 fatty acids in white shrimp feed to decrease cholesterol content and source of dietary fat to increase fat retention in meat. The research problem is whether the addition of CFO in white shrimp feed effect on the decrease cholesterol content and increase of fat retention in meat. This research aims to determine the effect of CFO in white shrimp feed to decrease cholesterol and increase of fat retention in meat. The method used is experimental method with Completely Randomized Design (CRD) as the experimental design. The treatment used is different persentage CFO addition to white shrimp feed, ie P0 (0%), P1 (2%), P2 (4%), P3 (6%) and P4 (8%) each treatment is repeated 4 times. Analysis of the data using Analysis of Varians (ANOVA) and to determine the best treatment performed Duncan's Multiple Range Test. Results showed that the addition of CFO in feed give significant effect (p <0.05) to decrease the cholesterol content in meat. The best average decrease of cholesterol content obtained at P3 (135.22 mg/100 g) and P4 (133.51 mg/100 g). Addition of CFO in feed did not give significant effect (p>0.05) to increase fat retention in meat.